Pengaruh Service Quality dan Customer Trust Terhadap Kepuasan Konsumen Maskapai Penerbangan Lion Air (Studi Kasus Bandara Internasional Raja Haji Fisabilillah Tanjungpinang) - Iranita Iranita (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2018)
Consumer satisfaction (Consumer Satisfaction) is a given positive attitude of consumers towards a service provided by a service company. Companies are expected to consider the factors that affect customer satisfaction. Lion Air, which is based on top brand award, is ranked first in the category of aviation services that use the LCC (low cost carrier). The almost all airports increase in passenger numbers in Indonesia, particularly in the international airport Raja Haji Fisabilillah Tanjungpinang. This study aims to examine the effect of service quality and customer trust to satisfaction of the consumer. The sample size is 60 people. This study uses a sampling method is the accidental sampling technique. technical analysis hypothesis testing using the Lisrel 8.5 program and Microsoft Excel version 2013. From this test later it can be seen how much the contribution of the independent variable (Service Quality, customer trust to the dependent variable (Lion Air Airlines customer satisfaction). The results showed that both directly and indirectly service quality and customer trust affect the satisfaction of customers of Lion Air